Fundamentals of IP and SoC Security Design, Verification, and Debug - Bhunia, Swarup; Ray, Sandip; Sur-Kolay, Susmita (Springer International Publishing : Imprint: Springer, 2017)
This book is about security in embedded systems and it provides an authoritative reference to all aspects of security in system-on-chip (SoC) designs. The authors discuss issues ranging from security requirements in SoC designs, definition of architectures and design choices to enforce and validate security policies, and trade-offs and conflicts involving security, functionality, and debug requirements. Coverage also includes case studies from the "trenches" of current industrial practice in design, implementation, and validation of security-critical embedded systems. Provides an authoritative reference and summary of the current state-of-the-art in security for embedded systems, hardware IPs and SoC designs; Takes a "cross-cutting" view of security that interacts with different design and validation components such as architecture, implementation, verification, and debug, each enforcing unique trade-offs;  Includes high-level overview, detailed analysis on implementation, and relevant case studies on design/verification/debug issues related to IP/SoC security.  .